269 MOLECULAR REQUIREMENTS FOR VLA-4-MEDIATED B-LYMPHOCYTE ADHERENCE UNDER FLOW CONDITIONS. Issue 1 (1st January 2007) - Mills, D. A.; Brown, D. C.; Ramirez, S.; Chigaev, A.; Sklar, L. A.; Laurence, M.; Larson, R. S.
Abstract : VLA-4 is critical for normal lymphocyte recirculation. Expressed on B lymphocytes, VLA-4 binds VCAM-1 on endothelium as a first step in lymphocyte extravasation. In this study, we examine the behavior of B lymphocytes on purified VCAM-1 as a first step toward quantifying the molecular parameters and requirements for lymphocyte rolling and arrest mediated by VLA-4. In our first set of observations, we wished to define chemokines that stimulated VLA-4 on human B lymphocytes isolated from blood and determine the site densities over which VLA-4-mediated attachment could occur. We tested a panel of chemokines and show that four chemokines may stimulate VLA-4 activation on human peripheral blood B lymphocytes. We next show that B lymphocytes isolated from peripheral blood will roll and attach to VCAM-1 in the absence of cellular stimulation; B-lymphocyte accumulation does not occur below 50 sites/μm 2 of VCAM-1 and shows increasing accumulation up to 200 sites/mm 2 . Interestingly, VLA-4 is activated to its high-affinity state using Mn 2+ or SDF-1α stimulation, and increased accumulation is seen over the range of 50 to 200 sites/μm 2 compared with no cellular stimuli, yet the site density over which attachment occurs remains unchanged. We then examined the effect of culturing B lymphocytes after isolation from blood on VLA-4-mediated binding. Using a VCAM-1 site density that would promote maximal binding (≈1, 200 sites/μm 2 ), we show that the proportion of VLA-4-expressing B lymphocytes that roll on VCAM-1 progressively increases from 1 to 4 days of culture (90% firm arrest/10% rolling on day 1 versus 45% firm arrest/55% rolling on day 4). Flow cytometry-based site density experiments indicate that the VLA-4 site density on B cells remains constant over the 4 days. To determine whether the change in VLA-4-mediated rolling and arrest on VCAM-1 was due to changes in the native receptor affinity or intracellular signaling, we performed a series of studies of pharmacologic studies. Exposure of day 1 or day 4 B lymphocytes to Mn 2+ and DTT, activators of VLA-4, promoted firm attachment of greater than 90% of the cells, indicating that VLA-4 could obtain a high-affinity state regardless of culture duration. Inhibition of protein kinase C, farnesyl transferase, and G protein-coupled receptor signaling increases the proportion of rolling cells with fewer overall attachments. This phenomenon is observed on day 1 and is more pronounced on day 4, suggesting that inside-out signaling remains intact despite culturing. In all, we quantify for the first time the effect of site density and postisolation culture on the behavior of VLA-4-mediated adherence of B lymphocytes. Our observations also suggest that signaling both from and to the VLA-4 receptor occurs and changes during postisolation culture. These observations are important in resolving previous studies examining VLA-4-mediated lymphocyte rolling and arrest.